Determinants of corporate cash holdings in tranquil and turbulent period: Evidence from an emerging economy - Khalil Jebran; Amjad Iqbal; Kalim Ullah Bhat; Muhammad Arif Khan; Mustansar Hayat (Financial Innovation, 2019)
Using a sample of 280 firms listed on the Pakistan Stock Exchange, we empirically investigate factors that determine corporate cash holdings in different periods from 2005 to 2014. We divide the sample into three sub-periods-pre-crisis, crisis, and post-crisis-and apply a panel data model to estimate the results. The results suggest that financial crises affect firms' cash holdings policies. Further, findings show that financial crisis has influenced the relationship of size and leverage with cash holdings. In particular, cash flow, liquidity, and tangibility are major determinants of cash holdings in the sub-periods. We present important implications for corporate managers, academicians, and policymakers.
Keywords: 650; Cash holdings; Financial crisis; Pakistan; Emerging economy